A multidisciplinary approach to quantify the permeability of the Whakaari/White Island volcanic hydrothermal system (Taupo Volcanic Zone, New Zealand) - Heap, Michael J.; Kennedy, Ben M.; Farquharson, Jamie I.; Ashworth, James; Mayer, Klaus; Letham-Brake, Mark; Reuschlé, Thierry; Gilg, H. Albert; Scheu, Bettina; Lavallée, Yan; Siratovich, Paul; Cole, Jim; et al. (Journal of Volcanology and Geothermal Research, 2017)
International audience Our multidisciplinary study aims to better understand the permeability of active volcanic hydrothermal systems, a vital prerequisite for modelling and understanding their behaviour and evolution. Whakaari/White Island volcano (an active stratovolcano at the north-eastern end of the Taupo Volcanic Zone of New Zealand) hosts a highly reactive hydrothermal system and represents an ideal natural laboratory to undertake such a study. We first gained an appreciation of the different lithologies at Whakaari and (where possible) their lateral and vertical extent through reconnaissance by land, sea, and air. The main crater, filled with tephra deposits, is shielded by a volcanic amphitheatre comprising interbedded lavas, lava breccias, and tuffs. We deployed field techniques to measure the permeability and density/porosity of (1) > 100 hand-sized sample blocks and (2) layered unlithified deposits in eight purpose-dug trenches. Our field measurements were then groundtruthed using traditional laboratory techniques on almost 150 samples. Our measurements highlight that the porosity of the materials at Whakaari varies from ∼ 0.01 to ∼ 0.7 and permeability varies by eight orders of magnitude (from ∼ 10 -19 to ∼ 10 -11 m 2 ). The wide range in physical and hydraulic properties is the result of the numerous lithologies and their varied microstructures and alteration intensities, as exposed by a combination of macroscopic and microscopic (scanning electron microscopy) observations, quantitative mineralogical studies (X-ray powder diffraction), and mercury porosimetry. An understanding of the spatial distribution of lithology and alteration style/intensity is therefore important to decipher fluid flow within the Whakaari volcanic hydrothermal system. We align our field observations and porosity/permeability measurements to construct a schematic cross section of Whakaari that highlights the salient findings of our study. Taken together, the alteration typical of a volcanic hydrothermal system can result ...